Community Structure of the Epipelic Diatom Vertically in the Intertidal Zone, West Dumai City, Riau Province - Wiranda Dellarosa; Sofyan Husein Siregar; Irvina Nurrachmi (Faculty of Fisheries and Marine, Universitas Riau, 2023)
The purpose of this study was to determine the community structure of epipelic diatoms vertically between stations. This research was carried out in March 2022 which is located in the waters of the City of West Dumai. The method used is the survey method. Determination of the sampling point is done by purposive sampling method and the determination of the station is based on anthropogenic input. A sampling of epipelic diatoms was carried out using a modified corer, then brought to the laboratory to identify and calculate the community structure, and the sediment samples were calculated for the content of nitrate, phosphate, organic matter, and sediment fractions. Sampling is accompanied by measurements of water quality consisting of brightness, temperature, current velocity, salinity and pH. 21 genera of epipelic diatoms were found in the waters of West Dumai City with an abundance value of 9,784 – 32,739 ind/cm2. The average value of the diversity index obtained was 2.6460 – 3.2065, the dominance index was 0.1478 – 0.2423, and the uniformity index was 0.7952 – 0.8424. The results of the one-way ANOVA test obtained an average value of 0.001, meaning that there was a significant difference in the abundance of epipelic diatoms between stations